A Piecewise Contractive Map on Triangles. Issue 2 (2nd July 2020) - Everett, Samuel
Abstract: We study the dynamics of a geometric piecewise map defined on the set of three pairwise nonparallel, nonconcurrent lines in R 2 . The geometric map of study may be analogized to the billiard map with a different reflection rule so that each iteration is a contraction over the space, thereby providing asymptotic behavior of interest. Our study puts particular emphasis on the behavior of periodic orbits generated by the map, with description of their geometry and bifurcation behavior. We establish that for any initial point in the space, the orbit will converge to a fixed point or periodic orbit, and we demonstrate that there exists an infinite variety of periodic orbits the orbits may converge to, dependent on the parameters of the underlying space.